Enantiosemy in Armenian Vocabulary - Mkrtchyan, Mkrtich (Bulletin of Yerevan University B: Philology, 2025)
Enantiosemy is a linguistic phenomenon when one meaning of the same word contradicts another. This phenomenon is present in almost all languages to varying degrees, although there is no clear record of its emergence and development. Studies on enantiosemy have been conducted using the material of the same language family, one language, or comparative analyses have been carried out on the material of different languages. In linguistics, there is no unified approach to understanding, describing, and classifying enantiosemy. The manifestations of enantiosemy have not yet been studied based on the material of the Armenian language, and this article is a unique attempt to fill this gap. The article begins by defining the phenomenon of “enantiosemy” in linguistic literature and then uses the descriptive method to classify words with enantiosemy from Ed. Aghayan’s “Explanatory Dictionary of Modern Armenian” into different groups. The article is significant not only in the sense that, for the first time, words with internal antonyms are identified using Armenian material but also because the material in the article can be used in the future in the teaching of Armenian, lexicography, and comparative studies of Armenian and other languages
Keywords: enantiosemy; contronym; lexicography; semantic variation; opposition